Changes produced by the pendulum appliance with skeletal anchorage and comparison with conventional pendulum appliance - Otazú Cambiano, Aldo Andres (2016)
The purposes of these investigations were firstly to evaluate the dentoalveolar, skeletal and soft tissue effects obtained with the bone-anchored pendulum appliance (BAPA) in patients with Class II malocclusion and secondly, to compare these effects with the conventional pendulum appliance (CPA). A sample of 18 patients (14 females; 4 males) with a mean age of 14.01 years (S.D 1.08) with Class II malocclusion treated with BAPA as distalizer device before fixed appliance in Orthodontic Department at the Dental School, University of São Paulo City. Lateral headfilms were taken at the beginning of treatment (T0) and at the end of distalization period (T1), measured and then statistically analyzed. Only the active distalization period was evaluated. The comparison group was composed by 18 patients (14 females; 4 males) with a mean age of 13.61 years (S.D 1.24) with the same malocclusion treated with CPA before fixed appliance in Orthodontic Department at Bauru Dental School, University of São Paulo. To evaluate the effects in this sample was used the same methodology abovementioned. Then, to compare changes between groups, the sample treated with CPA was named Group 1 (G1), and the sample treated with BAPA was named Group 2 (G2). The average distalization period was 5.76 and 6.16 months, respectively for G1 and G2. Both groups were compatibilized regarding initial age, treatment time, severity of Class II malocclusion and initial cephalometric characteristics. Intragroup comparisons were performed using dependent t tests and intergroup comparisons were performed using t tests. In G2 there was significant increase in the lower anterior face height, molar distalization, distal tipping and intrusion of the first and second maxillary molars. The first premolars had significant distalization and extrusion. Overbite significantly decreased and molar relationship was significantly improved. Comparing the groups, there were significantly greater maxillary first molar distalization, distal tipping and intrusion in G2 compared to G1. The maxillary incisors were labially tipped in G1 and lingually tipped in G2. The first premolars were distalized in G2 while were mesialized in G1. G1 showed a significantly greater overjet increase and smaller Class II molar relationship correction than G2. Distalization of the maxillary molars was successfully achieved in both groups, but using the BAPA several advantages were observed including exclusive maxillary molars distalization, spontaneous distal movement of the maxillary premolars, no undesirable side effects in the maxillary incisors and lips and establishment of a Class I molar relationship.